Corporate social responsibility and corporate cash holdings - Cheung, Adrian (Wai Kong) (Journal of Corporate Finance, 2016)
We identify three channels and the corresponding mechanisms through which corporate social responsibility (CSR) may affect corporate cash holdings. CSR firms are expected to have relatively low cash holdings because they tend to have low idiosyncratic risk due to their higher social capital with stakeholders. CSR firms also tend to have low systematic risk due to greater loyalty from CSR investors and/or customers. Lower systematic risk may increase or decrease cash holdings. Although low systematic risk induces firms to reduce their cash holdings, it also induces firms to hold a short debt maturity structure, with higher refinancing risks that higher cash holdings may mitigate. The agency view of CSR argues that entrenched managers in a firm with strong corporate governance may use CSR activities to collude with stakeholders in order to get higher managerial discretion (including cash) to extract private benefits. However, the corporate governance role of CSR implies that CSR is also effective in reducing the agency problems associated with the cash holdings decision. Using 2364 firms with 14,206 firm-year observations over the period 1991–2011, we establish that the positive effect of CSR on cash holdings via the systematic risk channel is robust, while the effects of CSR via the other two channels are not. Our findings are robust to different estimation methods and alternative measures of cash holdings, CSR, risks and corporate governance.